PEMBERDAYAAN LITERASI DIGITAL DAN PENINGKATAN REPRESENTASI PEREMPUAN MELALUI PELATIHAN PENULISAN ARTIKEL WIKIPEDIA PADA PROGRAM WIKIGAP 2026 - Fina Ruzika Zaimar; Wiwin Riski Windasari; Achmad Ridha; Siti Nur Reskiyawati Said; Andi Rahmatullah Mangga (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2026)
The gap in women’s representation in digital spaces remains a global challenge, including on open knowledge platforms such as Wikipedia. The limited number of articles about women, along with the low participation of female editors, contributes to inequality in information and knowledge representation. This community service activity aims to enhance participants’ digital literacy while providing skills in writing and editing articles on Wikipedia through the WikiGap 2026 program. The implementation method employed a participatory approach consisting of socialization, training sessions, hands-on article editing practice, and participant mentoring. The activity was conducted online and involved university students, school students, and the general public. The training materials covered an introduction to Wikipedia, principles of encyclopedic writing, source verification, editing techniques, and the publication of articles about women figures. The results of the activity indicated an improvement in participants’ understanding of digital literacy and their Wikipedia editing skills. Participants were able to create and improve articles related to women and gender equality issues in a more objective manner and based on reliable sources. The program also increased participants’ awareness of the importance of women’s representation in digital knowledge spaces. Therefore, the WikiGap 2026 training program serves as an effective form of community service in strengthening digital literacy while promoting information equality in digital media.